2020
DOI: 10.1038/s42003-020-0797-4
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenating the blood and bone marrow to slow aging-associated cognitive decline and Alzheimer’s disease

Abstract: Parabiosis, blood exchange and plasma transfer experiments have highlighted the rejuvenating properties of young blood. Our Communications Biology study demonstrated that young bone marrow transplantation attenuates cognitive decline in old mice, with preservation of hippocampal synapses and reduced microglial reactivity. We now discuss subsequent studies that shed additional light on how blood impacts cognitive function, and potential clinical applications, including ongoing clinical trials with young plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…One novel strategy could be in the form of transfusions of plasma or specific plasma constituents from young donors to elderly or AD recipients. Murine models of plasma transfusion including parabiosis studies have shown improvement in both neuropathological changes with reduction of Ab and tau burden and improvement in cognition (142,143). Various clinical trials exploring different types of therapeutic plasma exchange (TPE) in patients with established AD have generally yielded promising results, the findings of which are summarized by Imbimbo and colleagues (144).…”
Section: Novel Strategies For Remodulating the Cns Immune Responsementioning
confidence: 99%
See 2 more Smart Citations
“…One novel strategy could be in the form of transfusions of plasma or specific plasma constituents from young donors to elderly or AD recipients. Murine models of plasma transfusion including parabiosis studies have shown improvement in both neuropathological changes with reduction of Ab and tau burden and improvement in cognition (142,143). Various clinical trials exploring different types of therapeutic plasma exchange (TPE) in patients with established AD have generally yielded promising results, the findings of which are summarized by Imbimbo and colleagues (144).…”
Section: Novel Strategies For Remodulating the Cns Immune Responsementioning
confidence: 99%
“…Therefore, it has been posited that increased inflammatory cytokine levels in old plasma increase VCAM1 expression on BECs, resulting in peripheral leukocyte recruitment and BEC inflammation, in turn activating microglia (146). Another theory for the mechanism of TPE in AD is that old and young plasma may contain youthful and pro-aging factors that influence that ultimately influence the CNS environment and immune response (142). Just as old plasma may contain higher levels of pro-aging pro-inflammatory cytokines, young plasma may contain factors that promote healthy aging of the CNS (142).…”
Section: Novel Strategies For Remodulating the Cns Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Heterochronic (young to old) bone marrow transplant in 20-22 month old mice improves angiogenesis via upregulation of Cxcl12, Vegf and the inflammatory response post-MI [172,174,208]. Young bone marrow cell transplantation can also improve cognitive function and muscle repair in aged mice, implying a greater scope for bone marrow cell aging on systemic tissue aging [209][210][211]. Of note, cognitive improvements in old mice with young bone marrow is caused by changes in both neurons and microglia, the immune cell population in the brain [209,212].…”
Section: Bone Marrow Transplant and Niche Remodelingmentioning
confidence: 99%
“…The benefits of exercise on the aging brain are associated with increased neurogenesis, and plasticity, as well as improved learning and memory, but little information is known about the released factors that promote these effects. Corroborative evidence on plasma transfusions, parabiosis, and blood transfer studies show that young blood could possibly reduce age-related loss of excitability and plasticity, and can cause brain rejuvenation in aged animals, such as improving learning and memory performance in the hippocampus (Bouchard and Villeda, 2015;Kang et al, 2020). Pairing one young and one aged mouse in parabiosis led to several transcriptional changes linked to synaptic plasticity in the hippocampus of aged mice.…”
Section: The Beneficial Effects Of Plasma Factors On the Aged Brainmentioning
confidence: 99%